Risk scores and geriatric profile: can they really help us in anticoagulation decision making among older patients suffering from atrial fibrillation? - Maes F (Dove Medical Press, 2014)
Frédéric Maes,1,* Olivia Dalleur,2,3,* Séverine Henrard,4 Dominique Wouters,2 Christophe Scavée,1 Anne Spinewine,3,5 Benoit Boland4,6 1Cardiology, Cliniques universitaires Saint-Luc, Université catholique de Louvain, Brussels, Belgium; 2Pharmacy Department, Cliniques universitaires Saint-Luc, Université catholique de Louvain, Brussels, Belgium; 3Louvain Drug Research Institute, Université catholique de Louvain, Brussels, Belgium; 4Institute of Health and Society (IRSS), Université catholique de Louvain, Brussels, Belgium; 5Pharmacy Department, CHU Dinant-Godinne, Université catholique de Louvain, Yvoir, Belgium; 6Geriatric Medicine, Cliniques universitaires Saint-Luc, Université catholique de Louvain, Brussels, Belgium *The first two authors have contributed equally to the work Objectives: Anticoagulation for the prevention of cardio-embolism is most frequently indicated but largely underused in frail older patients with atrial fibrillation (AF). This study aimed at identifying characteristics associated with anticoagulation underuse.Methods: A cross-sectional study of consecutive geriatric patients aged ≥75 years, with AF and clear anticoagulation indication (CHADS2 [Congestive heart failure, Hypertension, Age >75, Diabetes mellitus, and prior Stroke or transient ischemic attack] ≥2) upon hospital admission. All patients benefited from a comprehensive geriatric assessment. Their risks of stroke and bleeding were predicted using CHADS2 and HEMORR2HAGES (Hepatic or renal disease, Ethanol abuse, Malignancy, Older (age >75 years), Reduced platelet count or function, Rebleed risk, Hypertension (uncontrolled), Anemia, Genetic factors, Excessive fall risk, and Stroke) scores, respectively. Results: Anticoagulation underuse was observed in 384 (50%) of 773 geriatric patients with AF (median age 85 years; female 57%, cognitive disorder 33%, nursing home 20%). No geriatric characteristic was found to be associated with anticoagulation underuse. Conversely, anticoagulation underuse was markedly increased in the patients treated with aspirin (odds ratio [OR] [95% confidence interval]: 5.3 [3.8; 7.5]). Other independent predictors of anticoagulation underuse were ethanol abuse (OR: 4.0 [1.4; 13.3]) and age ≥90 years (OR: 2.0 [1.2; 3.4]). Anticoagulation underuse was not inferior in patients with a lower bleeding risk and/or a higher stroke risk and underuse was surprisingly not inferior either in the AF patients who had previously had a stroke. Conclusion: Half of this geriatric population did not receive any anticoagulation despite a clear indication, regardless of their individual bleeding or stroke risks. Aspirin use is the main characteristic associated with anticoagulation underuse. Keywords: atrial fibrillation, anticoagulation, antiplatelet therapy, geriatric medicine, under-prescribing